Ultralong room temperature phosphorescence from amorphous organic materials toward confidential information encryption and decryption - Su, Yan; Phua, Soo Zeng Fiona; Li, Youbing; Zhou, Xianju; Jana, Deblin; Liu, Guofeng; Lim, Wei Qi; Ong, Wee Kong; Yang, Chaolong; Zhao, Yanli (Science advances, 2018)
Ultralong room temperature phosphorescence is achieved from amorphous organic materials toward information encryption. Ultralong room temperature phosphorescence (URTP) emitted from pure amorphous organic molecules is very rare. Although a few crystalline organic molecules could realize URTP with long lifetimes (>100 ms), practical applications of these crystalline organic phosphors are still challenging because the formation and maintenance of high-quality crystals are very difficult and complicated. Herein, we present a rational design for minimizing the vibrational dissipation of pure amorphous organic molecules to achieve URTP. By using this strategy, a series of URTP films with long lifetimes and high phosphorescent quantum yields (up to 0.75 s and 11.23%, respectively) were obtained from amorphous organic phosphors without visible fluorescence and phosphorescence under ambient conditions. On the basis of the unique features of URTP films, a new green screen printing technology without using any ink was developed toward confidential information encryption and decryption. This work presents a breakthrough strategy in applying amorphous organic materials for URTP.